Heineken N.V. equity research - brewing for a future! - Santos, Gonçalo Miguel Martins Duarte dos (2022)
This paper is part of a consolidated report called “Equity Research Heineken N.V”. In this project, we will analyze the company, study the market, see where it is growing, challenges it may face soon, and perform a valuation model on these premises. Heineken presents herself as the second-largest brewing company in the global market share, where the three most significant players account for more than 40% market. Nowadays, we are witnessing a growth in popularity for craft and premium beer. Overall, we believe that a company such as Heineken is a good investment opportunity. Currently, the stock is undervalued, and we believe that this company has better growth perspectives.